Empirical linkage between oil price and stock market returns and volatility: Evidence from international developed markets - Abderrazak Dhaoui; Naceur Khraief (Kiel Institute for the World Economy (IfW), 2014)
This paper examines empirically whether oil price shocks impact stock market returns. Using monthly data for eight developed countries from January 1991 to September 2013, strong negative connections between oil price and stock market returns are found in seven of the selected countries. Oil price changes are without significant effect on the stock market of Singapore. On the volatility of returns, the changes in oil prices are significant for six markets and they have not much effect on the others.
Keywords: G12; Q43; 330; oil price shocks; stock market return; EGARCH